Management of severe in-patient hyponatraemia: An audit in two teaching hospitals in Yorkshire, UK. (January 2015) - Narayanan, Deepa; Mbagaya, Wycliffe; Aye, Mo; Kilpatrick, Eric S.; Barth, Julian H.
Abstract Background. Hyponatraemia, the commonest electrolyte abnormality amongst in-patients, is associated with increased mortality. Until recently, there has been a lack of international consensus management of patients with severe hyponatraemia. Aim. We performed a retrospective study in two teaching hospitals in Yorkshire, UK, to evaluate the management of patients with severe hyponatraemia (serum Na ≤ 110 mmol/L) and to assess the frequency of complications observed in this group, in particular central pontine myelinolysis (CPM) and death. Methods. Retrospective data collection was performed on all of patients admitted with severe hyponatraemia in a calendar year in two teaching hospitals in Yorkshire. A detailed case note evaluation was conducted to determine the patient clinical characteristics, aetiology, investigations performed, treatment, complications and outcome of patients. Results. We identified 39 patients in total at both sites over a calendar year. There was a notable female predominance (n = 27), with the median (range) age being 65 (45–92) years and median sodium concentration 107 (94–110) mmol/L. Hyponatraemia was classified as acute (onset < 48 h) in six patients, chronic (onset > 48 h) in 20 patients and of unknown duration in 13 patients. Iatrogenic hyponatraemia secondary to drugs, especially thiazides was the most commonly observed aetiology. The mortality rate was 48.7% (n = 19) at the end of one year after admission episode and CPM was seen in 7.6% (n = 3) of patients. Conclusions. Severe hyponatraemia is associated with significant morbidity and mortality. Drug-induced hyponatraemia was the most common aetiology observed in our group of patients.